Natural dye-containing coating

JP2025021593APending Publication Date: 2025-02-14DIC CORP

Patent Information

Application Number
JP2023125395
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0024】 本発明によれば、フィコシアニンを色素として用いてなる天然色素含有塗料であって、天然色素含有塗料を提供することができる。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a natural dye-containing coating that comprises phycocyanin.SOLUTION: A natural dye-containing coating comprises a colorant and a coating vehicle, where the colorant comprises phycocyanin.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a paint containing a natural pigment that contains phycocyanin. [Background technology]

[0002] Traditionally, coloring materials such as dyes and pigments have been widely used to impart color to inks, paints, cosmetics, and other applications. Among these, synthetic colorants such as Blue No. 1 and Yellow No. 5 have also been used in food applications.

[0003] In recent years, there has been a strong tendency to avoid synthetic colorants due to concerns about their carcinogenicity, etc., and expectations are growing for natural dyes, which are thought to be safer. However, it is often difficult for natural dyes to maintain their vivid colors under various environments.

[0004] For example, phycocyanin, an algae pigment, is a natural blue pigment. Phycocyanin is a protein-bound pigment that is known to be able to be extracted from cyanobacteria such as spirulina. Phycocyanin is a pigment that exhibits a vivid blue color, and there are high expectations in the market for it as a sustainable pigment.

[0005] Phycocyanin is water-soluble, and when used in cosmetics or food dyes, there are concerns about dissolution into water and the associated color fading, but various methods have already been provided for making water-soluble dyes water-insoluble. For example, spherical silica particles with solid or hollow interiors can be obtained by spray-drying an aqueous solution of alkali silicate, and then immersing the particles obtained by spraying in an aqueous solution containing a sufficient amount of acid to remove the alkali in the particles, thereby removing the alkali and converting the particles into silica. In this case, it has been proposed that if a dye is dispersed in the aqueous solution of alkali silicate, dye-encapsulated silica particles colored in the same color tone as the dye used can be obtained (see, for example, Patent Document 1).

[0006] There is also provided a method for obtaining silica particles with immobilized dyes by imparting reactive functional groups to the surface of fine particles such as colloidal silica, immobilizing fluorescent dyes via these reactive functional groups, and then covering the surface with a silica coating (see, for example, Patent Document 2). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2013-095797 A [Patent Document 2] JP 2008-247713 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, there has not been enough research done on the blending of natural pigments containing phycocyanin into paints, and there has been a problem in that its usefulness has not been fully elucidated and utilized. Therefore, the problem to be solved by the present invention is to provide a paint containing a natural pigment that contains phycocyanin. [Means for solving the problem]

[0009] As a result of intensive research to solve the above problems, the present inventors have found that a paint containing a natural pigment can be obtained by incorporating a colorant containing phycocyanin and a paint vehicle, and have completed the present invention.

[0010] That is, the present invention includes the following aspects.

[0011] [1] A paint containing a natural pigment, comprising a colorant (A) and a paint vehicle, characterized in that the colorant (A) contains phycocyanin (B).

[0012] [2] The natural pigment-containing paint according to [1], wherein the phycocyanin (B) is derived from cyanobacteria of the genus Spirulina.

[0013] [3] The natural pigment-containing paint according to [1] or [2], wherein the phycocyanin (B) is Linablue G1 (trade name, manufactured by DIC Lifetech Co., Ltd.).

[0014] [4] The natural pigment-containing paint according to [1], characterized in that the colorant (A) is a water-insoluble pigment formed by complexing phycocyanin (B) and a silica structure (C).

[0015] [5] The natural pigment-containing paint according to [4], wherein the silica structure (C) is a two-phase continuous silica structure (D) consisting of a phase mainly composed of silica, the chemical bonds of which are Q4 bonds, and an air phase.

[0016] [6] The natural pigment-containing paint according to [5], wherein the diameter of the air phase in the bicontinuous silica structure (D) is in the range of 10 to 1000 nm.

[0017] [7] The specific surface area of ​​the two-phase continuous silica structure (D) is 0.1 to 200 m 2 The natural pigment-containing paint according to [5], wherein the range is 1 / g.

[0018] [8] The natural pigment-containing paint according to [5], wherein the silica-based phase of the two-phase continuous silica structure (D) contains 10 mass % or less of molybdenum oxide or vanadium oxide.

[0019] [9] The natural pigment-containing paint according to any one of [5] to [8], wherein the composition of the phycocyanin (B) and the bicontinuous silica structure (D) is, in terms of mass ratio, phycocyanin (B):bicontinuous silica structure (D)=0.1:99.9 to 90:10.

[0020]

[10] The natural pigment-containing paint according to [1], wherein the paint vehicle comprises 20 to 80% (by mass) of resin and 10 to 60% (by mass) of solvent.

[0021]

[11] The natural pigment-containing paint according to

[10] , wherein the resin contains a thermoplastic resin as an essential component and is one or more selected from an alkyd resin, an epoxy resin, an acrylic resin, a polyurethane resin, a polyester resin, a melamine resin, a urea resin, and a water-soluble resin.

[0022]

[12] The natural pigment-containing paint according to

[10] , wherein the solvent is one or more selected from the group consisting of hydrocarbons, alcohols, ketones, and water.

[0023]

[13] The natural pigment-containing paint according to

[11] , wherein the thermoplastic resin is one or more selected from polyester resin, polyamide resin, styrene resin, acrylic resin, polyolefin, polyalkylene terephthalate, and polyvinyl chloride resin. Effect of the Invention

[0024] According to the present invention, a natural pigment-containing paint can be provided, which uses phycocyanin as a pigment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The present invention will be described in detail below.

[0026] The present invention is a natural pigment-containing paint containing a colorant (A) and a paint vehicle, characterized in that the colorant (A) contains phycocyanin (B).

[0027] (Phycocyanin (B)) Examples of phycocyanin according to the present invention include phycocyanins derived from algae, such as phycocyanin derived from blue-green algae, phycocyanin derived from red algae, and phycocyanin derived from cryptophyte. Among these, phycocyanin derived from blue-green algae is preferred because it can be harvested in large quantities.

[0028] Examples of cyanobacteria include those of the genus Spirulina, Arthrospira, Aphanizomenon, Fisherella, Anabaena, Nostoc, Synechocystis, Synechococcus, Tolypothrix, Aphanothece, Mastigoclaus, Pleurocapsa, etc. Among them, cyanobacteria of the genus Spirulina and Arthrospira, which are produced on an industrial scale and have been confirmed to be safe, are preferred, and those of the genus Spirulina are more preferred.

[0029] In addition, as a raw material for preparing phycocyanin, raw cyanobacteria may be used, or dried cyanobacteria may be used. As for the dried product of cyanobacteria, raw cyanobacteria may be dried according to a conventional method, or a commercially available dried product may be used.

[0030] Phycocyanin can be obtained, for example, by suspending blue-green algae in water or a buffer solution such as a phosphate buffer or a citrate buffer, and extracting the phycocyanin from the blue-green algae.

[0031] The method for extracting phycocyanin is not particularly limited, and any commonly known method can be used.

[0032] A preferred embodiment of the extraction method is, for example, the extraction method described in JP 2006230272 A. Specifically, the extraction method described in the following extraction method (i) can be mentioned. By the extraction method (i), it is possible to obtain phycocyanin with high purity and vivid color tone.

[0033] <Extraction method (i)> The extraction method (i) is A first step of extracting phycocyanin from cyanobacteria into a water suspension; a second step of reacting a calcium salt with a phosphate in the extract to produce calcium phosphate and adsorbing impurities of phycocyanin to the calcium phosphate to obtain an adsorbate; and a third step of removing residual blue-green algae and adsorbed substances from the extract.

[0034] Furthermore, it is more preferable that the above extraction method (i) is the following extraction method (ii). <Extraction method (ii)> The extraction method (ii) is A first step of extracting phycocyanin from cyanobacteria into a water suspension; a second step of reacting a calcium salt with a phosphate in the extract to produce calcium phosphate and adsorbing impurities of phycocyanin to the calcium phosphate to obtain an adsorbate; The method includes a third step of removing residues of blue-green algae and adsorbed substances from the extract, and a step prior to the third step of adding a chelating agent to the extract.

[0035] The phycocyanin used in this invention was selected from the commercially available Linablue G1 (DIC Lifetech Co., Ltd., trehalose 55%, spirulina pigment 40%, trisodium citrate 5%) mixed with a stabilizer. As described in JP-A-11-299450, trehalose is used to increase thermal stability, and citric acid is used as a pH adjuster.

[0036] In the present invention, the colorant (A) may contain a component other than phycocyanin (B). More specifically, the colorant (A) may be a complex of phycocyanin (B) and silica structure (C). By complexing phycocyanin with the silica structure (C), the colorant (A) becomes a water-insoluble pigment, and the elution of phycocyanin into water and discoloration can be reduced.

[0037] The silica structure (C) is preferably a two-phase continuous silica structure (D) consisting of an air phase and a phase mainly composed of silica in which the chemical bonds are Q4 bonds.

[0038] The fact that the chemical bond of silica is composed of Q4 bonds means that it does not substantially have silanol groups. The silanol group is a functional group that is hydrophilic and has a high affinity for water. For this reason, for example, when a water-soluble dye is used in combination with a silica compound having a silanol group, the silica compound adsorbs or absorbs water, which makes the dye more likely to come off the silica, and as a result, it is thought that this may cause bleeding. On the other hand, it is difficult for silica composed of highly hydrophobic Q4 bonds to adsorb water-soluble dyes to its surface. In this situation, the specific structure of phycocyanin can interact with the biphasic silica structure (D) of the present application, and as a result, a complex of phycocyanin and biphasic silica structure (D) can be prepared in a simple manner, and this can be used as a water-insoluble dye. This is the present invention.

[0039] The bicontinuous silica structure (D) is not particularly limited as long as it is substantially free of silanol groups and the air phase and the silica phase are bicontinuous, as described above.

[0040] A simple method for obtaining such a two-phase continuous silica structure (D) is to use silica itself obtained by an existing silica synthesis method as a precursor raw material, utilize the affinity between a metal oxide that exhibits high-temperature sublimation and silica, and infiltrate the vapor of the metal oxide near the silanol group, scrape the silica there, convert the chemical bond of the silica into a Q4 bond, and penetrate a hollow tunnel from the outer surface of the structure to the entire inside, thereby making the two phases of silica and air continuous with each other.

[0041] The precursor raw material silica [hereinafter referred to as precursor silica (X)] is not particularly limited as long as it is amorphous silica, and for example, artificially synthesized silica-based materials such as silica gel, silica nanoparticles, mesoporous silica, and silica nanofibers, or naturally occurring silica such as biosilica, can be used.

[0042] The specific surface area of ​​the precursor silica (X) is not particularly limited, but it is preferable that the specific surface area is 10 m or more because the air phase can be easily formed as a continuous body (through holes). 2 / g or more, and particularly 100m 2 It is more preferable that the molecular weight is 1 / g or more.

[0043] The shape of the precursor silica (X) is not particularly limited. Since the overall shape of the silica (X) is maintained at a micron size or larger and a bicontinuous two-layer silica structure can be formed, it is preferable to select a precursor silica (X) having an appropriate shape depending on the purpose. For example, a spherical, amorphous, aspected structure (wire, fiber, ribbon, tube, etc.), sheet, etc. can be suitably used.

[0044] The whole size of the precursor silica (X) is not particularly limited.For example, when silica particles of micron size or more are used, a bicontinuous silica structure can be formed while maintaining the size of a single particle, and when silica particles of small particle size are used, a large bicontinuous silica structure can be formed by fusing a plurality of particles.

[0045] The precursor silica (X) may be composed of silica alone or may be a composite of silica and an organic compound. For example, an organic / inorganic composite obtained by modifying silica with an organic silane, a silica composite adsorbing a polymer, etc. may be suitably used. When using these composites, the content of the organic compound is not particularly limited, but from the viewpoint of efficiently producing the two-phase continuous silica structure (D), the content is preferably 60 mass% or less, more preferably 30 mass% or less.

[0046] In order to convert the precursor silica (X) into a silica structure composed of Q4 bonds, a metal oxide exhibiting high-temperature sublimability, particularly a molybdenum compound or vanadium compound (Y), is used. As the molybdenum compound, even if it is molybdenum oxide, it is preferable that the molybdenum metal is bonded with oxygen to form an acid radical anion (MOx n- Similarly, the vanadium compound may be a vanadium oxide or a compound containing an acid radical anion (MO x n- ) may be a compound containing the same.

[0047] The molybdenum metal is bonded to oxygen to form an acid radical anion (MO x n- The compound containing molybdenum oxide is not particularly limited as long as it can be converted to molybdenum oxide by high-temperature firing. For example, molybdic acid, H 3 PMo 12 O 40 , H 3 SiMo 12 O 40 , N.H. 4 Mo 7 O 12 Similarly, the vanadium metal may be bonded to oxygen to form an acid radical anion (MO x n- ) is a compound containing, for example, KVO 3 ,NaVO 3 ,NH 4 VO 3 Among these, when the cost aspect is taken into consideration, it is preferable to directly use molybdenum oxide or vanadium oxide. Moreover, since vanadium oxide is relatively highly toxic, it is more preferable to use molybdenum oxide.

[0048] By mixing the precursor silica (X) with a molybdenum compound or a vanadium compound (Y) and baking the mixture (Z), the silanol groups are substantially eliminated, and a two-phase continuous silica structure (D) consisting of a phase mainly composed of silica constituted by Q4 bonds and an air phase can be formed.

[0049] The mixture (Z) can be suitably used in such a ratio that the molybdenum compound or vanadium compound (Y) is added in an amount of 5 to 70% by mass, calculated as molybdenum oxide or vanadium oxide, relative to the precursor silica (X). In order to efficiently form the two-phase continuous silica structure (D), the amount is more preferably in the range of 10 to 50% by mass, and most preferably in the range of 15 to 30% by mass.

[0050] The process for preparing mixture (Z) is not particularly limited, and may be, for example, a dry mixing process without using a solvent, or a wet mixing process using a solvent.

[0051] The calcination may be performed at any temperature at which molybdenum oxide or vanadium oxide sublimes, specifically in the range of 600 to 1300° C., preferably in the range of 600 to 1300° C. In order to efficiently form the two-phase continuous silica structure (D), calcination at 800 to 1300° C. is more preferable. The atmosphere for the calcination is not particularly limited as long as oxygen is present, and an air atmosphere is more preferable in terms of safety and cost.

[0052] When a mixture (Z) of precursor silica (X) and molybdenum compound or vanadium compound (Y) is fired at 600°C or higher, molybdenum oxide or vanadium oxide forms an adhesion film on the surface of the pores of precursor silica (X). When silica having such an adhesion film on its surface is fired at a higher temperature, molybdenum oxide or vanadium oxide sublimes and the silanol groups in the silica essentially disappear, forming a two-phase continuous silica structure (D) with nano-sized cavities that are generally continuous (penetrating) through the silica structure and a three-dimensional silica network skeleton consisting of Q4 bonds. That is, it is believed that molybdenum oxide or vanadium oxide functions as a dehydration reaction catalyst for silanol groups during high-temperature firing. At this time, the chemical properties and nanostructure of the desired two-phase continuous silica structure (D) can be controlled by selecting the ratio of precursor silica (X) to molybdenum compound or vanadium compound (Y), the firing temperature, or the pore properties (pore size, distribution, etc.) of precursor silica (X).

[0053] The diameter of the air phase in the two-phase continuous silica structure (D) used in the present invention is in the range of 10 to 1000 nm, and particularly preferably in the range of 50 to 1000 nm. The diameter of the hollow tunnels (air phase) in the two-phase continuous silica structure (D) can be increased by increasing the firing temperature, increasing the content of the molybdenum compound or vanadium compound (Y) in the mixture (Z), or using a precursor silica (X) having a high specific surface area.

[0054] The silica network in the two-phase continuous silica structure (D) used in the present invention has nanowires as a basic structure, which form a three-dimensional network. The thickness of the nanowires is in the range of 5 to 1000 nm, and nanowires in the range of 30 to 500 nm are particularly preferably obtained. The thickness of the nanowire-like silica in the two-phase continuous silica structure (D) can be increased by increasing the firing temperature, increasing the content of the molybdenum compound or vanadium compound (Y) in the mixture (Z), or using a precursor silica (X) having a high specific surface area.

[0055] Compared with the precursor silica (X), the specific surface area of ​​the resulting bicontinuous silica structure (D) is significantly reduced. Depending on the properties of the precursor silica (X) and the firing conditions, the specific surface area of ​​the resulting bicontinuous silica structure (D) is 0.1 to 200 m 2 / g range, 0.1 to 50m 2 / g range is preferably obtained.

[0056] By high-temperature firing, most of the molybdenum compound or vanadium compound (Y) used is sublimated to form a silica structure mainly composed of silica. However, a small amount of molybdenum oxide or vanadium oxide that is not completely sublimed may be contained in the two-phase continuous silica structure (D). The content of these is 10% by mass or less, and in particular, the content of these can be reduced to 1% by mass or less by sufficient firing time and temperature.

[0057] The molybdenum oxide or vanadium oxide in the two-phase continuous silica structure (D) forms a non-crystalline structure on the outer surface and inside of the silica. These oxides can be removed by washing with an aqueous ammonia solution or an aqueous sodium hydroxide solution.

[0058] Molybdenum oxide or vanadium oxide functions as a dehydration catalyst at high temperatures, forming a two-phase continuous silica structure (D). The bonding state is 29 This can be confirmed by Si-CP / MAS NMR measurement. The three-dimensional silica network in the bicontinuous silica structure (D) itself is different from ordinary silica, and has a structure consisting of Q4 bonds, which is similar to the silica in quartz glass.

[0059] Ordinary silica gel has a very poor alkali resistance due to the presence of a large amount of silanol groups. In contrast, the two-phase continuous silica structure (D) used in the present invention has excellent alkali resistance because it has substantially no silanol groups. For example, in a sodium hydroxide aqueous solution of 0.1 mol / L or less, no hydrolysis is observed even at room temperature (25 to 30°C) for one month, and the initial two-phase bicontinuous structure can be maintained.

[0060] In addition, in a high-concentration aqueous sodium hydroxide solution of 0.1 mol / L or more, the surface of the silica wire in the bicontinuous silica structure (D) is etched, and the thickness of the wire, which is the basic structure of the silica network, can be changed to a thinner one while maintaining the shape of the bicontinuum.

[0061] In addition, since the structure (B) has substantially no silanol groups, the polarity of the structure surface is significantly reduced, and therefore the bicontinuous silica structure (D) has a much lower water vapor adsorption than the precursor silica (X).

[0062] Due to such properties, the bicontinuous silica structure (D) has excellent affinity with highly hydrophobic resins and other compounds, and can be easily mixed uniformly with them. That is, since ordinary silica has high surface polarity derived from surface silanol groups, it is difficult to mix uniformly with them, for example, when used as a filler for general-purpose polymers, unless the surface is modified. In contrast, the silica structure made of the Q4 structure used in the present invention can be used as a filler as it is. For example, it has been confirmed that when the bicontinuous silica structure (D) is mixed with polymethyl methacrylate (PMMA), PMMA diffuses throughout the through-holes (air phase) and forms a very uniform thin film on the surface of the nanowires, which are the basic structure of silica.

[0063] This means that the water-insoluble pigment formed by the complexation of phycocyanin (B) and the biphasic silica structure (D) of the present invention can be stably and uniformly mixed with various general-purpose resins and compounds, and can be suitably used as a colorant.

[0064] When the colorant (A) of the present invention is a water-soluble phycocyanin (B) complexed with a biphasic silica structure (D), it can be used as a water-insoluble pigment, and can be used for various purposes as a blue pigment using a natural pigment.

[0065] When using a two-phase continuous silica structure (D), the mass ratio of phycocyanin (B) to the two-phase continuous silica structure (D) can be arbitrarily designed. It is preferable that the mass ratio of phycocyanin (B): two-phase continuous silica structure (D) is 0.1:99.9 to 90:10. In particular, it is preferable that the ratio of (A):(B) is in the range of 0.1:99.9 to 50:50 in terms of the balance between coloring of the silica structure and water insolubility.

[0066] When the silica structure (C) or the two-phase continuous silica structure (D) is used, the method of mixing the phycocyanin (B) with the structure to obtain a complex is not particularly limited. For example, the simplest method is to mix them in an aqueous medium, and then filter and dry the obtained complex.

[0067] As a specific method for mixing each substance in an aqueous medium, 1) first, add the two-phase continuous silica structure (D) to water to prepare a dispersion. 2) On the other hand, dissolve phycocyanin or a preparation containing phycocyanin in water to prepare an aqueous solution. 3) Next, mix the above two liquids to form a composite. At this time, the structure dispersion liquid may be mixed with the phycocyanin-containing aqueous solution, or conversely, the structure dispersion liquid may be mixed with the phycocyanin-containing aqueous solution, or these two liquids may be mixed little by little to prepare. The temperature for mixing does not need to be particularly adjusted, but considering the decomposition temperature of phycocyanin alone, it is preferable to mix at 10 to 60 ° C, and more preferably 20 to 50 ° C. The time for mixing is not particularly limited, but is usually 5 minutes to 12 hours, and preferably 5 minutes to 8 hours. In addition, from the viewpoint of strengthening the interaction between phycocyanin (B) and the silica structure (B), it is preferable to leave it still after mixing. The temperature at which the mixture is left standing does not need to be particularly adjusted, but taking into consideration the decomposition temperature of phycocyanin alone, it is preferable to mix the mixture at 10 to 60° C., and more preferably at 20 to 50° C. The time at which the mixture is left standing is not particularly limited, but is usually 1 to 100 hours, and preferably 12 to 72 hours.

[0068] The resulting mixture is filtered and dried to obtain a complex which is a water-insoluble pigment. Since an excess amount of phycocyanin (B) is used, when the mixture is filtered through a filter such as a Nutsche filter, the filtrate is initially colored blue, but gradually becomes colorless and transparent. After the filtrate becomes colorless and transparent, the wet cake of the complex is washed with water again, and the filtrate is similarly colorless and transparent, and the wet cake of the complex is blue, so that it can be confirmed that the pigment phycocyanin (B) is complexed with the silica structure (C). The water-containing wet cake of the complex obtained is dried at room temperature, by heating, vacuum, reduced pressure drying, etc., to obtain a dry complex. The drying method and dryer can be any ordinary method and device, and are not limited.

[0069] The colorant of the present invention can be used according to the purpose, whether it is the above-mentioned wet cake containing water or a dry water-insoluble dye. When used in a water-based dispersion or ink, the wet cake can be used as it is, and when used in a solvent-based dispersion, it can be used after replacing the water-based with a solvent-based one. The dry water-insoluble dye can be used as it is, or can be redispersed in water, an organic solvent, a resin solution, etc.

[0070] Furthermore, the obtained colorant, particularly the water-insoluble pigment in the form of a complex, can of course be mixed with other organic pigments, inorganic pigments, dyes, and colorants in any ratio to obtain the desired hue. In addition, stabilizers and additives can be added to impart light resistance and heat resistance.

[0071] The stabilizer and additives can be added to either or both of the aqueous solution of the silica structure (C) and the aqueous solution containing phycocyanin, or they can be added to the water-insoluble pigment that is the obtained complex.

[0072] When the colorant of the present invention is used as a colorant for paint, it can be dispersed in a paint vehicle or the like.

[0073] (Paint vehicle) A paint vehicle is produced from raw materials such as 20 to 80 (mass) % resin and 10 to 60 (mass) % solvent.

[0074] The resin may contain a thermoplastic resin as an essential component. The resin may be one or more selected from an alkyd resin, an epoxy resin, an acrylic resin, a polyurethane resin, a polyester resin, a melamine resin, a urea resin, and a water-soluble resin.

[0075] The solvent may be one or more selected from the group consisting of hydrocarbons, alcohols, ketones, and water.

[0076] The thermoplastic resin may be one or more selected from polyester resin, polyamide resin, styrene resin, acrylic resin, polyolefin, polyalkylene terephthalate, and polyvinyl chloride resin.

[0077] The present invention will be described in more detail below with reference to synthesis examples and formulation examples, but the present invention is not limited to these synthesis examples and formulation examples.

[0078] (Preparation of silica structures) 8 g of Sunsphere H-121 (AGC Si-Tech, spherical, average particle size 12 μm) and 2 g of molybdenum oxide (Nihon Inorganic Chemical Co., Ltd.) were mixed in a mortar to obtain 10 g of a mixture (Z-1) of precursor silica and molybdenum oxide. 1 g of the obtained mixture (Z-1) was fired at 1000°C for 5 hours in an electric furnace. Most of the molybdenum oxide was sublimated, and about 7.6 g of silica structure powder was obtained. SEM and TEM observation confirmed that the obtained silica structure had hollow tunnels penetrating from the outer surface to the entire inside, and had a two-phase cocontinuous structure in which the two phases of silica and air were continuous with each other.

[0079] The powder of the bicontinuous silica structure obtained above was used to 29 When Si CP / MAS NMR was performed, no peaks due to Q2, Q3, or Q4 were observed within the range from 80 ppm to 120 ppm (Note: 29In principle, in Si CP / MAS NMR, the presence of silanol groups causes the spin transfer of protons, resulting in the observation of a Q4 bond signal. When silanols are completely eliminated, silica contains only Q4 bonds, but in this case, there is no spin transfer from the surrounding protons, and the Q4 chemical shift signal cannot be observed. This suggests that the silanol groups in the silica structure have been completely eliminated by the molybdenum oxide treatment, and the obtained silica structure resembles quartz glass, which contains only Q4 bonds.

[0080] In addition, the BET measurement showed that the surface area of ​​the silica gel before the molybdenum oxide treatment was approximately 800 m 2 / g, whereas the BET surface area of ​​the bicontinuous silica structure obtained above is about 25.4 m 2 This means that the wire-like silica is dense in the bicontinuous silica structure, and that no micropores exist in the wire-like silica.

[0081] Furthermore, when a water vapor adsorption measurement test was performed on the obtained bicontinuous silica structure, it was found that the precursor silica gel adsorbed a large amount of water, whereas the silica structure treated with molybdenum oxide hardly adsorbed any water, suggesting that the surface polarity of the obtained silica structure is very low.

[0082] In addition, the molybdenum oxide remaining in the obtained bicontinuous silica structure was analyzed. TEM-EDS analysis revealed that molybdenum oxide was present both inside and on the surface of the wire-like Q4 silica. High-resolution TEM observation confirmed that the structure of the remaining molybdenum oxide was amorphous, not crystalline. Furthermore, fluorescent X-ray quantitative evaluation data confirmed that the amount of molybdenum oxide in the bicontinuous silica structure was 1.0 mass%.

[0083] (Synthesis Example 1: Preparation of Colorant (1)) In a 13.5 mL screw tube, 500 mg of the silica structure obtained above, 1.25 g of Lina Blue G1 (DIC Life Tech Co., Ltd., trehalose 55%, spirulina pigment 40%, trisodium citrate 5%), 5 mL of ion-exchanged water, and a stirrer were added. The solution was stirred and mixed for 10 minutes at room temperature (20 ° C), and left to stand for 24 hours under light-shielded conditions. The mixture was filtered through filter paper and washed with 200 mL of ion-exchanged water until the washing liquid was no longer colored. The solid after filtration was dried in a vacuum dryer (740 mmHg) at 20 ° C for 12 hours to obtain powder (1). The obtained powder (1) exhibited the same blue color as phycocyanin. In addition, when this was added to water and stirred, and then left to stand for 1 hour, powder (1) settled and the supernatant became colorless and transparent, confirming that powder (1) is a water-insoluble pigment.

[0084] (Synthesis Example 2: Preparation of Colorant (2)) Powder (2) was obtained in the same manner as in Synthesis Example 1, except that the stirring time was changed from 10 minutes to 7 hours and the standing time was changed from 24 hours to 57 hours. The obtained powder (2) exhibited the same blue color as phycocyanin. In addition, when this was added to water and stirred and then left to stand for 1 hour, powder (2) settled and the supernatant became colorless and transparent, confirming that powder (2) is a water-insoluble pigment.

[0085] (Synthesis Example 3: Preparation of Colorant (3)) In a 100 mL eggplant flask, 500 mg of the silica structure obtained above, 1.25 g of Lina Blue G1, 5 mL of ion-exchanged water, and a stirrer were added. The solution was stirred and mixed for 10 minutes at room temperature (20 ° C), vacuumed with an aspirator for 15 minutes, and left to stand for 62 hours under light-shielded conditions. After that, after vacuuming with an aspirator for 2 hours, the mixture was filtered with filter paper and washed with 200 mL of ion-exchanged water until the washing liquid was no longer colored. The solid after filtration was dried in a vacuum dryer (740 mmHg) at 20 ° C for 12 hours to obtain powder (3). The obtained powder (3) exhibited the same blue color as phycocyanin. In addition, when this was added to water and stirred, and then left to stand for 1 hour, powder (3) settled and the supernatant became colorless and transparent, confirming that powder (3) is a water-insoluble pigment.

[0086] (Mixing Example 1: Preparation of paint containing natural pigment (1)) Colorant (1) obtained in Synthesis Example 1: 20.0 parts by weight Polyester resin 30.0 parts by weight Acrylic resin 35.0 parts by weight Water 15.0 parts by weight

[0087] (Mixing Example 2: Preparation of paint containing natural pigment (2)) Colorant (2) obtained in Synthesis Example 2: 20.0 parts by weight Polyester resin 30.0 parts by weight Acrylic resin 35.0 parts by weight Water 15.0 parts by weight

[0088] (Mixing Example 3: Preparation of paint containing natural pigment (3)) Colorant (3) obtained in Synthesis Example 3: 20.0 parts by weight Polyester resin 30.0 parts by weight Acrylic resin 35.0 parts by weight Water 15.0 parts by weight

Claims

1. A natural pigment-containing paint containing a colorant (A) and a paint vehicle, A natural pigment-containing paint, characterized in that the colorant (A) contains phycocyanin (B).

2. 2. The natural pigment-containing paint according to claim 1, wherein the phycocyanin (B) is derived from cyanobacteria of the genus Spirulina.

3. The natural pigment-containing paint according to claim 1 or 2, wherein the phycocyanin (B) is Lina Blue G1 (trade name, manufactured by DIC Lifetech Co., Ltd.).

4. The natural pigment-containing paint according to claim 1, characterized in that the colorant (A) is a water-insoluble pigment formed by complexing phycocyanin (B) and a silica structure (C).

5. The natural pigment-containing paint according to claim 4, wherein the silica structure (C) is a two-phase continuous silica structure (D) consisting of a phase mainly composed of silica, the chemical bond of which is Q4 bond, and an air phase.

6. 6. The natural pigment-containing paint according to claim 5, wherein the diameter of the air phase in the bicontinuous silica structure (D) is in the range of 10 to 1000 nm.

7. The specific surface area of ​​the bicontinuous silica structure (D) is 0.1 to 200 m 2 The natural pigment-containing paint according to claim 5, wherein the total molecular weight of the paint is in the range of 1 / g.

8. 6. The natural pigment-containing paint according to claim 5, wherein the silica-based phase of the bicontinuous silica structure (D) contains 10 mass % or less of molybdenum oxide or vanadium oxide.

9. The composition of the phycocyanin (B) and the two-phase continuous silica structure (D) is, in terms of mass ratio, phycocyanin (B): two-phase continuous silica structure (D) = 0.1: 99.9 to 90:

10. The natural pigment-containing paint according to any one of claims 5 to 8.

10. 2. The natural pigment-containing paint according to claim 1, wherein the paint vehicle comprises 20 to 80% (by mass) of resin and 10 to 60% (by mass) of solvent.

11. The resin contains a thermoplastic resin as an essential component, The natural pigment-containing paint according to claim 10, which is one or more selected from the group consisting of alkyd resins, epoxy resins, acrylic resins, polyurethane resins, polyester resins, melamine resins, urea resins, and water-soluble resins.

12. The natural pigment-containing paint according to claim 10, wherein the solvent is at least one selected from the group consisting of hydrocarbons, alcohols, ketones, and water.

13. The paint containing a natural pigment according to claim 11, wherein the thermoplastic resin is at least one selected from the group consisting of polyester resin, polyamide resin, styrene resin, acrylic resin, polyolefin, polyalkylene terephthalate and polyvinyl chloride resin.

Citation Information

Patent Citations

  • Fluorescent coloring material-containing nano-silica particle, and method for preparing the same

    JP2008247713A

  • Method for producing dye-including silica-based particle, dye-including silica-based particle, and use of the particle

    JP2013095797A

Cited By

  • Anti-counterfeiting viscose composite sewing thread and preparation method thereof

    CN122169266A